2023
DOI: 10.1001/jamanetworkopen.2023.27358
|View full text |Cite
|
Sign up to set email alerts
|

Probability of 5% or Greater Weight Loss or BMI Reduction to Healthy Weight Among Adults With Overweight or Obesity

Lyudmyla Kompaniyets,
David S. Freedman,
Brook Belay
et al.

Abstract: ImportanceInformation on the probability of weight loss among US adults with overweight or obesity is limited.ObjectiveTo assess the probability of 5% or greater weight loss, 10% or greater weight loss, body mass index (BMI) reduction to a lower BMI category, and BMI reduction to the healthy weight category among US adults with initial overweight or obesity overall and by sex and race.Design, Setting, and ParticipantsThis cohort study obtained data from the IQVIA ambulatory electronic medical records database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Among 31 284 patients with obesity in 2017 and follow-up weight data in 2019, 25.9% achieved 5% or greater weight loss. Prior work has shown that between 10% and 27% of patients with obesity achieve 5% or greater weight loss over 6 months to 5 years, with a greater annual probability of achieving 5% or greater weight loss observed among individuals with a higher baseline BMI (≥35) …”
Section: Discussionmentioning
confidence: 99%
“…Among 31 284 patients with obesity in 2017 and follow-up weight data in 2019, 25.9% achieved 5% or greater weight loss. Prior work has shown that between 10% and 27% of patients with obesity achieve 5% or greater weight loss over 6 months to 5 years, with a greater annual probability of achieving 5% or greater weight loss observed among individuals with a higher baseline BMI (≥35) …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that lifestyle and behavioral modifications will be crucial in secondary prevention and management of overweight and obesity also in the future. However, the probability of reaching normal weight or maintaining substantial weight loss among adults with overweight or obesity was found to be very low when patients receiving bariatric surgery were excluded [ 41 , 42 ]. The methods available to enhance behavioral and lifestyle changes evidently needs innovation to improve in both clinical and public health contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that reducing daily energy intake by 500 kcal through dietary control was effective in reducing body weight by more than 5%, even if additional meals were offered to compensate for the energy expenditure caused by exercise ( Table 3 ), which is consistent with the findings of Tang et al [ 26 ]. A 5% weight loss is widely recognized as the threshold at which clinically meaningful health improvements, including a decrease in systolic and diastolic blood pressure, fasting blood glucose, and glycated hemoglobin, as well as increase in high-density lipoprotein cholesterol, can be obtained [ 27 , 28 ]. However, most of the individuals were unable to achieve desirable weight loss via lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%